2022
DOI: 10.1002/slct.202201963
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Dots‐Decorated g‐C3N4 as Peroxidase Nanozyme for Colorimetric Detection of Cr(VI) in Aqueous Medium

Abstract: Carbon dots (CD) generated from biomass were fabricated on g-C 3 N 4 to construct a metal-free nanozyme with inherent peroxidase mimic functions. The formation of CD/g-C 3 N 4 was confirmed by different characterization techniques. The CD/g-C 3 N 4 displays distinct peroxidase mimic activities, as evidenced by the catalyzed oxidation of TMB (3,3',5,5', -tetramethylbenzidine) in the presence of H 2 O 2 , as well as color alteration from transparent to blue. The mechanistic analysis of peroxidase activity indica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…g-C 3 N 4 was produced via thermal polymerization of urea. 43 A conventional procedure involved placing 20 g of urea in a silica crucible with a covered lid placed in a muffle furnace and calcining it for two hours at 550 °C at a heating rate of 50 °C min −1 . After cooling, yellow-colored bulk g-C 3 N 4 was generated.…”
Section: Methodsmentioning
confidence: 99%
“…g-C 3 N 4 was produced via thermal polymerization of urea. 43 A conventional procedure involved placing 20 g of urea in a silica crucible with a covered lid placed in a muffle furnace and calcining it for two hours at 550 °C at a heating rate of 50 °C min −1 . After cooling, yellow-colored bulk g-C 3 N 4 was generated.…”
Section: Methodsmentioning
confidence: 99%
“…Second, introduction of Cr 6+ can affect the kinetics of nanozyme-catalyzed reactions, 35,[37][38][39] providing a strategy to achieve the sensing of toxic Cr 6+ . For instance, Amini and coworkers found that hexacyanoferrate-inserted Ni/Al layered double hydroxides (Ni/Al-Fe(CN) 6 LDH) exhibited certain peroxidase-like activity in triggering the oxidation of nonfluorescent terephthalic acid (TA) to TAOH with a fluorescence emission in the presence of H 2 O 2 .…”
Section: Detection Of Inorganic Ionsmentioning
confidence: 99%